LOCAL WISDOM IN LEARNING: A REVIEW OF LEARNING FORMS AND TECHNIQUES - Erni, Sukma; Ernita, Mahdar; Munajar, Adhi; Nasution, Anisah; Selviani, Rini (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2026)
The article is based on the assumption that the current generation is increasingly distant from its own culture as a result of technological developments. By using the distribution of open google form questioners for teachers at the elementary to university levels, 53 teachers/lecturers were obtained who filled out. The data is mapped according to the existing theme to see teachers' innovations in designing the learning process by making local wisdom materials part of the learning process. The findings obtained are that teachers learn local wisdom by enriching, inserting and integrating with the material learned. The forms of wisdom used include teaching/taboos, culinary, traditions, carvings, medicines, crafts, games, folklore, batik, including measuring instruments. Through learning that adds local wisdom to the teaching material, teachers realize how important it is to remind students of the importance of local wisdom so that it is maintained from generation to generation.